2016
DOI: 10.1088/1674-1056/25/2/024304
|View full text |Cite
|
Sign up to set email alerts
|

Bubble nonlinear dynamics and stimulated scattering process

Abstract: A complete understanding of the bubble dynamics is deemed necessary in order to achieve their full potential applications in industry and medicine. For this purpose it is first needed to expand our knowledge of a single bubble behavior under different possible conditions including the frequency and pressure variations of the sound field. In addition, stimulated scattering of sound on a bubble is a special effect in sound field, and its characteristics are associated with bubble oscillation mode. A bubble in li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Hongray et al [9] , [10] provided a radial model for a spherical charged bubble and found that the charges distributed at the bubble interface were able to enhance the ultrasonic cavitation effect. In addition, various mathematical models were proposed to describe the oscillation of a spherical cavitation bubble in a compressible liquid [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Hongray et al [9] , [10] provided a radial model for a spherical charged bubble and found that the charges distributed at the bubble interface were able to enhance the ultrasonic cavitation effect. In addition, various mathematical models were proposed to describe the oscillation of a spherical cavitation bubble in a compressible liquid [11] , [12] , [13] , [14] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is more accurate to use the nonlinear effects for the bubble distribution inversion. [16] Most of the studies of the nonlinear scattering cross-section method do not consider the influence of non-resonant bubbles, [18,19] or the transfer matrix with good condition number and good robustness cannot be obtained after the integral discretization, so the nonlinear inversion has not been widely used yet. [20][21][22] The contribution of this paper is that the nonlinear coefficients are selected as the basis of inversion based on the unique nonlinear acoustic effect of bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical works have described the interaction between two or many gas bubbles in liquid. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] In the present work, the theoretical framework of the model of bubblebubble interaction [9] is applied to describe the interaction between a particle and an oscillating bubble driven by ultrasound waves in liquid. Both the particle and the bubble are free to translate.…”
Section: Introductionmentioning
confidence: 99%